Modelling the behavior of metal-oxide-semiconductor structures under thermal field treatment - Олег Викторович Александров; Никита Николаевич Морозов (Physics of Complex Systems)
A quantitative model of the behavior of metal-oxide-semiconductor (MOS) structures subjected to thermal field treatment, particularly in the accumulation and recovery modes of mobile charge in the gate dielectric, is presented. The mobile charge transport is modelled based on ion trapping on polyenergetic defects with a spectrum of binding energies. The time-dependent shifts in the threshold voltage of the MOS structures under positive and subsequent negative gate biases are simulated. The proposed model accounts for both symmetric and asymmetric behaviours observed in MOS structures containing Na+ ions. Additionally, the model determines the range of binding energies, trap concentrations, and the spatial localization of traps.